2009
DOI: 10.1590/s1516-35982009000700028
|View full text |Cite
|
Sign up to set email alerts
|

Utilização de óleo de soja em rações para vacas leiteiras no período de transição: consumo, produção e composição do leite

Abstract: Use of soybean oil for dairy cows during transition period: Intake, milk yield and composition ABSTRACT -The objective of this study was to evaluate the productivity of dairy cows supplemented with soybean oil during the transition period. Twenty multiparous and pregnant Holstein cows were randomly allocated to two diets: control (C), 2.5% ether extract (EE) in the dry matter (DM); and fat (G), with the addition of 3% soybean oil, and 5.5% EE in the dry matter. The average values for intake were not different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
(16 reference statements)
0
3
1
1
Order By: Relevance
“…Similar to our findings, but with Jersey cows, Botaro et al (2011), in a study in the state of São Paulo from 2007 to 2008 found higher fat contents in the milk from Jersey cows (3.97%) compared to Holstein and Girolando cows, which showed no significant difference from each other (3.54 and 3.45%, respectively). The result of this study in relation to the fat percentage of milk from Holstein cows (2.93%) was lower than that found by Santos et al (2009), who observed high fat content in the milk from Holstein cows (4.30%) using soybean oil in the diets of cows during the transition period. Paula et al (2008) and Stelzer et al (2009) observed similar fat contents (3.40%), but higher than those found in this work.…”
Section: Resultscontrasting
confidence: 88%
“…Similar to our findings, but with Jersey cows, Botaro et al (2011), in a study in the state of São Paulo from 2007 to 2008 found higher fat contents in the milk from Jersey cows (3.97%) compared to Holstein and Girolando cows, which showed no significant difference from each other (3.54 and 3.45%, respectively). The result of this study in relation to the fat percentage of milk from Holstein cows (2.93%) was lower than that found by Santos et al (2009), who observed high fat content in the milk from Holstein cows (4.30%) using soybean oil in the diets of cows during the transition period. Paula et al (2008) and Stelzer et al (2009) observed similar fat contents (3.40%), but higher than those found in this work.…”
Section: Resultscontrasting
confidence: 88%
“…Staples et al (2001) cited that the productive answer to the utilization of supplemental dietary fat for lactating cows can result in increases in milk yield from 2.0 to 2.5 kg/cow/day. Santos et al (2009) evaluated the inclusion of 3.30% soybean oil, in total dry matter basis, in the diet of dairy cows in the transition period and early lactation. The authors observed that the animals fed soybean oil diet produced 2.53 kg/d more milk than those fed control diet (7.93%).…”
Section: Introductionmentioning
confidence: 99%
“…In evaluating DMI (g/kg 0.75 ) had significant effect (P <0.05) of breed and treatment with advancing pregnancy. Morada Nova ewes exhibited a lower consumption according to Santos et al (2009) reporting that near parturition, there was a decrease without any metabolic disorder has been confirmed. This fact emphasizes the adaptive capacity of these animals with little decrease in the DMI, once that the low offer of energy derived from the diet associated with a decrease in nutrient intake could promote serious metabolic disorders.…”
Section: Resultsmentioning
confidence: 88%